Solusi IoT untuk adaptasi New Normal - Adhie Tri Wahyudi; Erni Suparti; Bagus Ismail Adhi Wicaksana (Program Studi Teknik Industri Universitas Setia Budi, 2020)
Internet of Things (IoT) is a concept that utilizes internet network connectivity for a unified system communication. Analysis conducted on the keyword